Game development toolkit design and implementation - Ong, Ansel Hong Xiang (2019)
This project, as the name suggests is the research and design of a toolkit that is designed specifically to help create serious games. Serious games, or applied games, are games whose primary purpose is anything but purely entertainment. We will discuss what is the difference between serious games and simulators, as well as the essential elements of a serious game. There are existing toolkits to aid game creation, but nothing like what this project is trying to do. This report will first explain what serious games are and they’re effectiveness. Followed by the 7 modules that will be needed in the toolkit. And the research and work that I have done. We will then focus on what is “flow” and how to achieve it with the customization module with the DDA component as well as how the plan implantation portion of the module is being designed.